(untitled) (Journal of Pharmaceutical Negative Results, 2021)
It has been determined that burnout is very common among doctors and other health professionals. Relatively little, though, has been written about psychologist burnout. The current study examines the research on burnout, stressors, and professional wellness in active psychologists. Stress levels, burnout, and work satisfaction among health service psychologists in academic health centers (AHCs) were investigated based on a survey of Association for Psychologists in Academic Health Centers members (n = 93). Respondents reported varying degrees of burnout: 0% reported no symptoms, 59% reported occasional stress, 12% reported symptoms that persisted, 18% reported burning out, and 3% reported being totally burned out. The majority of respondents talked about working "at full capacity" (41%) or being "overextended" (39%). Notwithstanding these reservations, the majority of respondents expressed satisfaction with their jobs (42% “very satisfied,” 44% “somewhat satisfied”) and suggested careers as medical psychologists (50% strongly; 34% moderately). Clinical load, pay, lack of protected time for research, teaching, education, and supervision, lack of psychologists to meet demand, and non-billable clinical activities were the most frequently cited sources of stress. Workload and burnout were linked to lower levels of professional satisfaction, which is in line with the literature on physicians. The current study examines findings from the larger literature on burnout among health professionals and fills a gap in the literature on the stress psychologists encounter in AHCs. More knowledge is required regarding the variables that influence health service psychologist burnout, risk factor identification and modification, and preventative measures.